Design and evaluation of Bilayered tablets of Simvastatin - Anna balaji; Sreekanth Goud.P (International Journal of Pharmacy and Analytical Research, 2014)
The Objective of this study was to formulate bilayer tablets comprising of Simvastatin in both Extended Release layer and immediate release layer and to carry out in vitro dissolution studies for the formulated tablets as per official specifications. Bilayer tablets comprised two layers, i.e. immediate release and extended release layer. Simvastatin is an orally active anti hypertensive agent. For immediate release drug and polymer ratio (Simvastatin: croscarmellose sodium in the formulations I1 to I3 was prepared in the ratio (1:1, 1:2, 1:3). Whereas for extended release, drug and polymer ratio (Simvastatin: HPMC K4M) were formulated as 1:0.5, 1:1, 1:1.5, 1:2 and 1:2.5 in Formulations C1 to C5. The immediate release layer comprised sodium starch glycolate and croscarmellose sodium as super disintegrant and sustained release layer comprised ethyl cellulose and HPMC K4M as release retardant polymers. Direct compression method was used for formulation of bilayer tablets. Accelerated stability studies were carried out in accordance with ICH guidelines. Ethyl cellulose and HPMC K4M retarded the release of Simvastatin from the controlled release layer for 12 hrs. After stability tests, degradation of both drugs were found but the drugs, contents were found to be within the range. Drug release mechanism release exponent (n) were determined for all formulations (0.689-0.789). The immediate release layer of Simvastatin was found to follow a first order release model and the extended release layer of Simvastatin was found to follow zero order release model.